2019
DOI: 10.1101/683656
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early alterations in cortical and cerebellar regional brain growth in Down Syndrome: An in-vivo fetal and neonatal MRI assessment

Abstract: Down Syndrome (DS) is the most frequent genetic cause of intellectual disability with a wide spectrum of neurodevelopmental outcomes. At present, the relationship between structural brain morphology and the spectrum of cognitive phenotypes in DS, is not well understood. This study aimed to quantify development of the fetal and neonatal brain in DS using dedicated, optimised and motion-corrected invivo magnetic resonance imaging (MRI). We detected deviations in development and altered regional brain growth in t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 72 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…A total of 804 studies were initially screened and 59 publications were included in the final systematic review 4,5,7,15‐69 (Figure 1) (Table S1). Separate publications with duplicated data from those included were assessed 51,70‐80 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 804 studies were initially screened and 59 publications were included in the final systematic review 4,5,7,15‐69 (Figure 1) (Table S1). Separate publications with duplicated data from those included were assessed 51,70‐80 …”
Section: Resultsmentioning
confidence: 99%
“…Four studies showed measurements of the PF correlated with a diagnosis of more systemic abnormalities compared to controls – congenital heart disease, 51 Down syndrome 66 and fetuses small for GA 33,43 …”
Section: Resultsmentioning
confidence: 99%